PENERAPAN TEKNOLOGI TEPAT GUNA UNTUK PENINGKATAN KOMODITAS RUMPUT LAUT DI DESA TIROWALI KECAMATAN PONRANG KABUPATEN LUWU - Sudirman, Andi Mangnguntungi; Jumardi, Andi; Asia , Nur; Damis, Damis (Jurnal Abdi Insani, 2024)
One of the agricultural sectors that has commodity potential is seaweed. Seaweed is a plant that is classified as benthic macroalgae which generally lives in brackish waters or uses coastal areas. Tirowali Village, Ponrang District, Luwu Regency is a coastal area that cultivates seaweed of the Eucheuma cottonii type. However, seaweed farmers often experience losses due to several factors including air quality and pest disturbances, partners' limited knowledge in using technology such as measuring air quality in the form of unstable water salt levels on cultivated land due to the rainy season, and partners' expertise in handling seaweed. After harvest, we still use soil as a medium to dry the harvest. This causes the quality of the dried seaweed to be poor and some of the harvest tends to rot due to direct contact with the soil. Apart from that, the time needed to dry seaweed takes 2-3 days. Indirectly affects market prices. The solution to this problem is to provide training and assistance in seaweed cultivation, the harvesting process at the ideal age, and the handling of seaweed that is attacked by pests and diseases. Furthermore, providing training and assistance by utilizing appropriate technology such as the Fluval Sea Hydrometer Salt Water air temperature detector to increase the growth and quality of seaweed production, providing training on the use of post-harvest Rotary Dryer seaweed drying technology, especially to help farmers if the weather is cloudy or rain, provide training related to digital marketing-based marketing strategies to widely market products using online and offline methods.